Effects of amino group on the properties of carbon nanotubes. Issue 4 (2nd April 2016) - Qi, Hongxia; Zhao, Bo
ABSTRACT: The surfaces of multi-walled carbon nanotubes were grafted with amino functional groups by reacting acyl-chloride-functionalized carbon nanotubes (CNTs) with hexamethylene diamine, which improves the surfactivity of CNTs. The dispersity, surface morphology, and thermogravimetry of acid-treated and amino-functionalized CNTs were investigated. Amino-functionalized CNTs were added into epoxy resin to analyze the effects of amino functional groups on the properties of resin composites. It was found that the properties of CNTs, such as morphology and scale, were not affected by amino functional groups, but the dispersity in water was highly improved. Amino-functionalized CNTs are better dispersed in resin matrix, and the mechanical properties of composites are improved significantly, whereas the conductivity of composites is not enhanced as expected.